Passive Polarized Light Guiding and Thermally Induced Visible Fluorescence in Histidine Microstructures with Optical Switching Function. (23rd December 2020) - Handelman, Amir; Lapsker, Igor; Jacob, Avi; Laikhtman, Alexander
Abstract: The increasing interest in implantable medical devices that incorporate photonic components has accelerated the search for new, biocompatible optical materials at micro‐ and nano‐scale. This work proposes use of the polar amino acid L‐histidine as a candidate for bio‐photonic devices. L‐histidine is self‐assembled into diverse solid‐state crystallized microstructures, one of which—the elongated hexagonal microplate—is shown to have passive waveguiding capability of polarized light. The interaction of polarized light with histidine microplates having different orientations and thicknesses is studied from Stokes parameters and Mueller matrix. The linear birefringence of histidine microplates is estimated by using the theory of generalized Jones matrix for biaxial crystals. Visible fluorescence in heated histidine microplates is discovered and its origin is discussed. The phenomenon of passive waveguiding capability of polarized light by such an elongated hexagonal microplate means that the microplate can be used as a part of an optical switch. The findings show that besides the known chemical and biological characteristics of the amino acid histidine, it also has optical properties that can be exploited in multifunctional biophotonic applications, such as waveguides, polarizers, interconnects, and light sources. Abstract : The optical properties of amino acid histidine microstructures are investigated. It is demonstrated that these self‐assembled microplates are capable of passively guiding polarized light and show visible fluorescence upon heating. The polarized light‐matter interaction is analyzed and birefringence is estimated. The findings show that histidine can be exploited in multifunctional biophotonic applications, such as waveguiding, polarizers, and light source.